Ответ:
Пошаговое объяснение:
у = 8; y' = 0
y = 15x; y' = 15
y = ∛x; y' = 1/(3∛x²)
y = 3ˣ; y'= 3ˣ* ln3
y= x⁵; y' = 5x⁴
y = ∛x² = 2/3∛x
y = 1/4x; y' = - 1/4x²
y = (x³-1)/(x³+2);
![y' = \left[\begin{array}{ccc}(\frac{u}{v})' = \frac{v'-u'}{v^{2} } \\u= x^{3-1} \\v= x^{3} +2\end{array}\right] = y' = \left[\begin{array}{ccc}(\frac{u}{v})' = \frac{v'-u'}{v^{2} } \\u= x^{3-1} \\v= x^{3} +2\end{array}\right] =](https://tex.z-dn.net/?f=y%27%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D%28%5Cfrac%7Bu%7D%7Bv%7D%29%27%20%3D%20%5Cfrac%7Bv%27-u%27%7D%7Bv%5E%7B2%7D%20%7D%20%20%5C%5Cu%3D%20x%5E%7B3-1%7D%20%5C%5Cv%3D%20x%5E%7B3%7D%20%2B2%5Cend%7Barray%7D%5Cright%5D%20%3D)
после подстановок и вычислений получим
![y' = \frac{9x^{2} }{(2+x^{3} )^{2} } y' = \frac{9x^{2} }{(2+x^{3} )^{2} }](https://tex.z-dn.net/?f=y%27%20%3D%20%5Cfrac%7B9x%5E%7B2%7D%20%7D%7B%282%2Bx%5E%7B3%7D%20%29%5E%7B2%7D%20%7D)
y = (4x+x²)(x⁵+x)
![y' =\left[\begin{array}{ccc}(uv)'=uv'+u'v\\u=x^{2}+4x \\v=x^{5}+x \end{array}\right] y' =\left[\begin{array}{ccc}(uv)'=uv'+u'v\\u=x^{2}+4x \\v=x^{5}+x \end{array}\right]](https://tex.z-dn.net/?f=y%27%20%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D%28uv%29%27%3Duv%27%2Bu%27v%5C%5Cu%3Dx%5E%7B2%7D%2B4x%20%5C%5Cv%3Dx%5E%7B5%7D%2Bx%20%5Cend%7Barray%7D%5Cright%5D)
после подстановки и вычислений получим
y' = x(8+3x+24x⁴ + 7x⁵)